Sport and identity in ancient Greece - Papakonstantinou, Zinon, author.
1 online resource
Keywords: "From the eighth century BCE to the late third century CE, Greeks trained in sport and competed in periodic contests that generated enormous popular interest. As a result, sport was an ideal vehicle for the construction of a plurality of identities along the lines of ethnic origin, civic affiliation, legal and social status as well as gender. Sport and Identity in Ancient Greece delves into the rich literary and epigraphic record on ancient Greek sport and examines, through a series of case studies, diverse aspects of the process of identity construction through sport. Chapters discuss elite identities and sport, sport spectatorship, the regulatory framework of Greek sport, sport and benefaction in the Hellenistic and Roman world, embodied and gendered identities in epigraphic commemoration, as well as the creation of a hybrid culture of Greco-Roman sport in the eastern Mediterranean during the Roman imperial period. This book will be of great interest to students of Ancient Greek society and identity, as well as the history of sport"--